Comparative Study of the Steel Sheet Pile Wall with Concrete and Polymer Sheet Pile Wall - Roslan, Athirah; Ling, Felix Ngee Leh (Recent Trends in Civil Engineering and Built Environment, 2022)
A suitable type of sheet pile walls, namely steel, concrete and polymer need to be chosen based on the site condition, application and its allowable and ultimate moment depending on the lateral earth pressure. Deformation of sheet pile walls depends on its material characteristics and differs for ductile materials and rigid materials. Hence, it is crucial to study the effect of material type on the deformation and stress distribution of cantilever sheet pile walls. A case study at Yan, Kedah was utilized as a base model and parametric study was conducted numerically by adding a 6 m long sheet pile wall at the toe of embankment with different material types. The simulation analysis was carried out by using PLAXIS 2D. The results of analysis had shown that different material types of sheet pile wall had shown differences in terms of deformation, bending moment, shear force and axial force when subjected to the same loading condition. Hence, it is advisable to carefully choose the materials of sheet pile walls depending on the requirement of the project.